Determinants and Causality of Current Account Balance and Foreign Direct Investment: Lower Middle Income Countries in ASEAN - Aimon, Hasdi; Putri Kurniadi, Anggi; Ulfa Sentosa, Sri (KnE Social Sciences, 2020)
This study investigates the determinants and causality between current account balance and foreign direct investment in Association of Southeast Asian Nations (ASEAN) in lower middle income countries. This study uses time series from 2000-2017 and cross section of 6 countries, namely Indonesia, Philippines, Vietnam, Lao, Myanmar and Cambodia, which were analyzed using simultaneous equation model approach. There are three important findings in this study. First, current account balance is positively affected by financial development, government expenditure, real GDP and real exchange rate, while negatively affected by foreign direct investment. Second, foreign direct investment is positively affected by real GDP, real exchange rate, economic openness and current account balance, while negatively affected by inflation. Third, there is a causal relationship between current account balance and foreign direct investment, which the two variables significantly influence each other. Therefore, it is highly recommended for lower middle income countries in ASEAN to intervene in macroeconomic policy variables, so that the deficit conditions for current account balance and foreign direct investment can be reduced in the lower middle income countries in ASEAN. Keywords: current account balance, foreign direct investment, determinants, causality, lower middle income countries, ASEAN.